Segregação espacial urbana na cidade de São Paulo no final do século XX: a cidade formal e os enclaves fortificados como representação hegemônica do espaço urbano (1986-1995) - Yoshioka, Luma de Sousa (2019)
This research intends to analyze through Folha de São Paulo's and O Estado de São Paulo's newspaper's classified advertisements (1986-1995), how articulations between the State and the Real Estate Market influenced the spatial segregation in São Paulo city. Therefore, we are interested in observing how this process occurred through planned and infrastructure region promotion, and also by looking at the diffusion of dwelling as reservation values for middle and upper classes at the end of the 20th Century — a period of economic recession and crisis for the Real Estate Market, that lead to the closure of BNH (Banco Nacional de Habitação or National Housing Bank). In the same way, we are looking to correlate the matter of the rising number of fortified enclaves — which can be found in the newspaper's real estate advertisements that created the corpus for this study and also in the documents of the formal city formation — as a collaborator factor to the development of a hegemonic view of the city of São Paulo. Thus, based on urbanism patterns, it is possible to assign the occurrence of wicked public policies to this perspective, that turned access to housing and urban infrastructure to working-class into a precarious process, increasing the Real Estate speculation and leading to a physiognomy transformation of the city. This transformation reverses the logic between private and public to create highly segregated spaces of admission and exclusion. Given that we are analyzing these relations, we may state that housing became strongly associated with the idea of a highly safe and profitable investment during this economic recession. By that logic, a private property linked to a spatial capitalist production, that was diffused since improvement interventions and a modern progressive project for the city became the only possible path to access the legitimated and formal city, which includes adequate housing conditions, safety, and urban infrastructure